Islamic fintech potential in Bosnia and Herzegovina - Omercic, Jasmin (Islamic Finance News, 2023)
Fintech fuses financial services and information technology (IT) innovatively and creatively to develop in previously unseen ways through platforms which augment and showcase unthought potential in nations like Bosnia and Herzegovina (B&H).